Prayer and mental health: An introduction to this special issue of Mental Health, Religion & Culture - Lewis, Christopher Alan (Mental health, religion & culture, 2008)
The purpose of this special issue of Mental Health, Religion and Culture was to provide a forum for examples of current research and theorizing examining the relationship between prayer and mental health. This collection, comprising one review article, one theoretical article, eight empirical articles, and six book reviews, is drawn from researchers in the Netherlands, UK, and USA. A variety of different measures of prayer and mental health were employed among various samples. In combination, these studies clearly attest to the importance of prayer to mental health. In combination, this work demonstrated the wide range of matters currently being investigated by researchers, as well as the variety of methodologies being employed within the social scientific study of religion and related disciplines focused on the relationship between prayer and mental health.